The Effect of Soaking Time and Liquid Smoke Types on the Quality of Smoked Skipjack (Kastuwonus pelanis L.) Fillets During Storage - Naema Bora; John Tibo Kana Tiri; Eny Idayati (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
This study aims to determine the effect of soaking time in distilled and non-distilled liquid smoke of kusambi wood (Schleicera oleosa) on the quality of smoked skipjack fillets. This study used an experimental method designed with a completely randomized design (CRD) with two factor treatments. The first factor was soaking time with four levels, namely 10, 20, 30 and 40 min. The second treatment factor was the type of liquid smoke from kusambi wood (without and with distillation). The variables observed in this study focused on the quality of the smoked skipjack fillets after the 8-day storage period, including: water content (%), pH, total acid (%), fat content (%) protein (%) and phenol content (%). The results showed that the liquid smoke of kusambi wood with distillation had a pH of 3.18 which was more acidic and had higher phenol content (0.61%) and acid content (17.62%) than liquid smoke without distillation. Of the eight treatment combinations, the quality of smoked skipjack fillets after 8 days of storage, it is found that the treatment of soaking 30 min and 40 min in distilled liquid smoke is the best treatment and meets the quality requirements of SNI. This is based on the value of water content (48.46% and 49.67%), pH (4.04 and 3.96), total acid (8.84% and 9.07%), fat content (4.85% and 4.92%), protein content (18.04% and 17.83%) and phenol content in smoked skipjack fillets (0.65% and 0.61%). Keywords: liquid smoke, distillation, soaking time, quality of smoked skipjack fillet